2020
DOI: 10.1128/mbio.03107-19
|View full text |Cite
|
Sign up to set email alerts
|

A Polar Flagellar Transcriptional Program Mediated by Diverse Two-Component Signal Transduction Systems and Basal Flagellar Proteins Is Broadly Conserved in Polar Flagellates

Abstract: Bacterial flagella are rotating nanomachines required for motility. Flagellar gene expression and protein secretion are coordinated for efficient flagellar biogenesis. Polar flagellates, unlike peritrichous bacteria, commonly order flagellar rod and hook gene transcription as a separate step after production of the MS ring, C ring, and flagellar type III secretion system (fT3SS) core proteins that form a competent fT3SS. Conserved regulatory mechanisms in diverse polar flagellates to create this polar flagella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…An additional tier, Class III, activated by the FleSR (also known as FlrBC) twocomponent system is required in P. aeruginosa, V. cholerae, V. parahemolyticus and A. hydrolitica to complete the assembly of the components of the hook-basal body (HBB) complex (Dasgupta et al, 2003;Khan et al, 2020;Wilhelms et al, 2011). Activation of FleSR/FlrBC was recently shown to respond to the assembly of the EBB in V. cholerae and P. aeruginosa (Burnham et al, 2020), as previously observed with the Epsilonproteobacteria Campylobacter jejuni and Helicobacter pylori (Boll and Hendrixson, 2013;Tsang and Hoover, 2015). Sensing of the assembly status may be mediated by FlrD, a membrane protein containing a HAMP domain that stimulates FlrBC-dependent activation in V. cholerae (Moisi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…An additional tier, Class III, activated by the FleSR (also known as FlrBC) twocomponent system is required in P. aeruginosa, V. cholerae, V. parahemolyticus and A. hydrolitica to complete the assembly of the components of the hook-basal body (HBB) complex (Dasgupta et al, 2003;Khan et al, 2020;Wilhelms et al, 2011). Activation of FleSR/FlrBC was recently shown to respond to the assembly of the EBB in V. cholerae and P. aeruginosa (Burnham et al, 2020), as previously observed with the Epsilonproteobacteria Campylobacter jejuni and Helicobacter pylori (Boll and Hendrixson, 2013;Tsang and Hoover, 2015). Sensing of the assembly status may be mediated by FlrD, a membrane protein containing a HAMP domain that stimulates FlrBC-dependent activation in V. cholerae (Moisi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Sigma factor 70 controls biosynthesis of the flagellar export apparatus, FlhF, and Rpo N (σ54). Current models of C. jejuni flagellar biosynthesis show that the type III flagellar secretion system and its assembly with the inner membrane anchor and motor protein complexes, together with FlhF, influence the activity of the FlgSR two-component signal transduction pathway; FlgR in turn is required to stimulate activity of the alternative sigma factor, σ54 ( Rpo N) ( Gilbreath et al, 2011 ; Burnham et al, 2020 ). The σ54 regulon is almost exclusively composed of flagellar structural genes in C. jejuni , and expression of these genes generates essential components of flagella, including the basal body, hook and minor flagellin subunits ( Chaudhuri et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, polar flagellated bacteria that contain the FlhF/FlhG regulatory system mostly possess TCSs, such as FleS/R in P. aeruginosa , FlgS/R in C. jejuni , or FlrB/C in V. cholerae . Such TCSs serve as an additional check point in flagellar biogenesis and are essential to allow rod and hook subunit expression, which are sigma 54 dependant, after correct assembly of the MS-ring/rotor/fT3SS complex [ 67 ]. Peritrichous bacteria do not possess a similar regulatory mechanism because rod and hook subunits are co-expressed with basal body components.…”
Section: Dynamics Of Flagellar Assemblymentioning
confidence: 99%
“…In P. aeruginosa , FleS is a cytoplasmic protein that senses intracellular signals and transfers its phosphate to FleR. However, the interaction between FleS and FliG/M/fT3SS has not yet been shown, but Burham et al demonstrated the importance of primary assembly in the activation of these TCSs [ 67 ]. Although this mechanism has not yet been elucidated in Pseudomonas , FlgS has been shown to physically interact with FliF and FliG in Campylobacter jejuni only if multimerized around the fT3SS.…”
Section: Dynamics Of Flagellar Assemblymentioning
confidence: 99%